1992
DOI: 10.1111/j.1365-2052.1992.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Synteny mapping of the bovine IGHG2, CRC and IGF1 genes

Abstract: A panel of bovine‐murine hybrid cell lines was analysed for 10 loci, including three (IGF1, IGHG2 and the calcium release channel gene [CRC]) that have previously been mapped in man, but not in cattle. The IGF and CRC genes were indirectly mapped to chromosomes 5 and 18 respectively and the syntenies of the HOX2 and GH genes and of the NP and FOS genes were confirmed. The results also show that the IGHG2 locus, which is linked to NP and FOS on human chromosome 14, is separated from these genes in cattle. By sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The activity of this gene in the adipose tissue and the subsequent increase in deposition of triglycerides are promoted by insulin [43]. Some studies have suggested that the FAs synthesis in the subcutaneous adipose tissue on beef is not sensitive to insulin levels [44, 45]. In this sense, the activity of LPL gene in the muscle tissue appears not to be insulin dependent [43], however, many authors have provided evidence to support the opposite [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of this gene in the adipose tissue and the subsequent increase in deposition of triglycerides are promoted by insulin [43]. Some studies have suggested that the FAs synthesis in the subcutaneous adipose tissue on beef is not sensitive to insulin levels [44, 45]. In this sense, the activity of LPL gene in the muscle tissue appears not to be insulin dependent [43], however, many authors have provided evidence to support the opposite [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of recombinant GH in dairy farms has confirmed the key role of the somatotrophic axis in this physiological function (Bauman, 1999;Baldi, 1999). IGF-I is a well-known somatomedin (Sorensen et al, 1992;Renaville, 1997;Curi et al, 2005); it is expressed by a gene located on chromosome 5 that shows an SnaBI polymorphysm in the 5' flanking region (Miller et al, 1992;Ge et al, 1997). Parmentier et al (1999) reviewed the somatotrophic axis and its relationship with milk production and selection; this pathway and particularly IGF-I, the 7649-Da single-chain peptide and its gene, appear to be promising for association with reproductive traits in Angus beef cattle (Yilmaz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine insulin-like growth factor 1 (IGF1) gene is localized in chromosome 5 and consists of 6 exons (Bishop et al, 1991;Miller et al, 1992). IGF1 has been shown to be a candidate gene for growth rate and meat production traits due to its role in regulation of cell proliferation and animal growth (Siadkowska et al, 2006).…”
Section: Introductionmentioning
confidence: 99%